Multifunctional Superparamagnetic Iron Oxide Nanoparticles Conjugated with Aβ Oligomer-Specific scFv Antibody and Class A Scavenger Receptor Activator Show Early Diagnostic Potentials for Alzheimer’s Disease - Liu XG (Dove Medical Press, 2020)
Xiao-Ge Liu,1,2 Lun Zhang,1,2 Shuai Lu,1 Dong-Qun Liu,1,2 Ling-Xiao Zhang,1,2 Xiao-Lin Yu,1 Rui-Tian Liu1 1State Key Laboratory of Biochemical Engineering, Institute of Process Engineering, Chinese Academy of Sciences, Beijing 100190, People’s Republic of China; 2School of Chemistry and Chemical Engineering, University of Chinese Academy of Science, Beijing 100049, People’s Republic of ChinaCorrespondence: Rui-Tian Liu; Xiao-Lin Yu Tel/ Fax +86 10 82545017; +86 10 82545075Tel/ Fax +86 10 82545025Email rtliu@ipe.ac.cn; yuxiaolin@ipe.ac.cnBackground: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder and the most common cause of dementia. Diagnosing AD before symptoms arise will facilitate earlier intervention. The early diagnostic approaches are thus urgently needed.Methods: The multifunctional nanoparticles W20/XD4-SPIONs were constructed by the conjugation of oligomer-specific scFv antibody W20 and class A scavenger receptor (SR-A) activator XD4 onto superparamagnetic iron oxide nanoparticles (SPIONs). The SPIONs’ stability and uniformity in size were measured by dynamic light scattering and transmission electron microscopy. The ability of W20/XD4-SPIONs for recognizing Aβ oligomers (AβOs) and promoting AβOs phagocytosis was assessed by immunocytochemistry and flow cytometry analysis. The blood–brain barrier permeability of W20/XD4-SPIONs was determined by a co-culture transwell model. The in vivo probe distribution of W20/XD4-SPIONs in AD mouse brains was detected by magnetic resonance imaging (MRI).Results: W20/XD4-SPIONs, as an AβOs-targeted molecular MRI contrast probe, readily reached pathological AβOs regions in brains and distinguished AD transgenic mice from WT controls. W20/XD4-SPIONs retained the property of XD4 for SR-A activation and significantly promoted microglial phagocytosis of AβOs. Moreover, W20/XD4-SPIONs exhibited the properties of good biocompatibility, high stability and low cytotoxicity.Conclusion: Compared with W20-SPIONs or XD4-SPIONs, W20/XD4-SPIONs show the highest efficiency for AβOs-targeting and significantly enhance AβOs uptake by microglia. As a molecular probe, W20/XD4-SPIONs also specifically and sensitively bind to AβOs in AD brains to provide an MRI signal, demonstrating that W20/XD4-SPIONs are promising diagnostic agents for early-stage AD. Due to the beneficial effect of W20 and XD4 on neuropathology, W20/XD4-SPIONs may also have therapeutic potential for AD .Keywords: magnetic resonance imaging, diagnosis, Alzheimer’s disease, β-amyloid, oligomer, class A scavenger receptor